Suppose we denote a n as the value of r = 0 ∑ n n C r 1 , express r = 0 ∑ n n C r r in terms of n and/or a n .
Clarification :
n C r denote the binomial coefficient, ( r n ) = r ! ( n − r ) ! n ! .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Ankit Nigam , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.
For quick solution, substitute n= 1 and match the given options..
We can solve this by induction. Let b n = r = 0 ∑ n n C r r . And let us consider a n b n .
\(\begin{array} {} \dfrac {b_0}{a_0} = \dfrac {\frac{0}{1}}{\frac{1}{1}} & = 0 & \Rightarrow b_0= (0)a_0 = \frac{1}{2}(0)a_0 \\ \dfrac {b_1}{a_1} = \dfrac {\frac{0}{1}+\frac{1}{1}}{\frac{1}{1}+\frac{1}{1}} & = \frac{1}{2} & \Rightarrow b_1= \frac{1}{2}a_1 = \frac{1}{2}(1)a_1 \\ \dfrac {b_2}{a_2} = \dfrac {\frac{0}{1}+\frac{1}{2}+\frac{2}{1}}{\frac{1}{1}+\frac{1}{2}+\frac{1}{1}} & = 1 & \Rightarrow b_2= a_2 = \frac{1}{2}(2)a_2 \\ \dfrac {b_3}{a_3} = \dfrac {\frac{0}{1}+\frac{1}{3}+\frac{2}{3}+\frac{3}{1}}{\frac{1}{1}+\frac{1}{3}+\frac{1}{3}+\frac{1}{1}} & = \frac{3}{2} & \Rightarrow b_3= \frac{3}{2} a_3 = \frac{1}{2}(3)a_3 \\ \dfrac {b_4}{a_4} = \dfrac {\frac{0}{1}+\frac{1}{4}+\frac{2}{6}+\frac{3}{4}+\frac{4}{1}}{\frac{1}{1}+\frac{1}{4}+\frac{1}{6}+\frac{1}{4}+\frac{1}{1}} & = 2 & \Rightarrow b_4 = 2 a_4 = \frac{1}{2}(4)a_4 \\ ... \end{array} \)
⇒ b n = r = 0 ∑ n n C r r = 2 1 n a n
This is not induction. You should show that the pattern always work for all integers as oppose to show that it appears to work for a small amount of integers.
Thanks for the solution sir. Its like JEE style, I did it in some generalized way...
I t i s g i v e n t h a t a n = ( n 0 ) 1 + ( n 1 ) 1 + . . . . . . . . . ( n n ) 1
Let S= ∑ r = 0 n ( n r ) r
∴ S = ( n 0 ) 0 + ( n 1 ) 1 + ( n 2 ) 2 . . . . . . . . + ( n n ) n
or S = ( n n ) n + ( n n − 1 ) n − 1 + ( n n − 2 ) n − 2 + . . . . . . ( n 0 ) 0
= ( n 0 ) n + ( n 1 ) n − 1 + ( n 2 ) n − 2 + . . . . . . ( n n ) 0 [ ∵ ( n r ) = ( n n − r ) ]
∴ 2 S = ( n 0 ) n + ( n 1 ) n + ( n 2 ) n + . . . . . ( n n ) n
∴ 2 S = n ⎣ ⎡ ( n 0 ) 1 + ( n 1 ) 1 + ( n 2 ) 1 + . . . . . . . . ( n n ) 1 ⎦ ⎤
∴ 2 S = n [ a n ]
∴ S = 2 n a n
MY FIRST SOLUTION ON BRILLIANT :D
Problem Loading...
Note Loading...
Set Loading...
Thanks for the solution sir. Its like JEE style, I did it in some generalized way...
I t i s g i v e n t h a t a n = ( n 0 ) 1 + ( n 1 ) 1 + . . . . . . . . . ( n n ) 1
Let S= ∑ r = 0 n ( n r ) r
∴ S = ( n 0 ) 0 + ( n 1 ) 1 + ( n 2 ) 2 . . . . . . . . + ( n n ) n
or S = ( n n ) n + ( n n − 1 ) n − 1 + ( n n − 2 ) n − 2 + . . . . . . ( n 0 ) 0
= ( n 0 ) n + ( n 1 ) n − 1 + ( n 2 ) n − 2 + . . . . . . ( n n ) 0 [ ∵ ( n r ) = ( n n − r ) ]
∴ 2 S = ( n 0 ) n + ( n 1 ) n + ( n 2 ) n + . . . . . ( n n ) n
∴ 2 S = n ⎣ ⎡ ( n 0 ) 1 + ( n 1 ) 1 + ( n 2 ) 1 + . . . . . . . . ( n n ) 1 ⎦ ⎤
∴ 2 S = n [ a n ]
∴ S = 2 n a n
MY FIRST SOLUTION ON BRILLIANT :D